The Role of Social Media in Increasing the Effectiveness of Islamic Communication Among Millennials - Karmuji Abu Safar; Sunardi Bashri Iman; Asep Masykur; Sarbini Anim; Mastori (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to explore the forms and characteristics of Islamic communication among the millennial generation, especially in the context of social media use and the dynamics of communication patterns that emerge in the digital era. The millennial generation, who grew and developed along with the advancement of information technology, has a different communication style compared to the previous generation. They tend to prioritize communication that is visual, interactive, and involves active participation. In the realm of Islamic preaching, this condition is a challenge as well as an opportunity for preachers to adjust their message delivery methods. This study uses a qualitative approach based on literature studies by reviewing relevant literature related to Islamic communication, generation theory, and the use of social media in preaching. The findings of this study reveal that the success of Islamic communication to the millennial generation is highly dependent on the preacher's ability to convey messages contextually, use inclusive language, and maximize the use of digital media as the main medium. In addition, an approach that touches the emotional side and encourages active audience involvement is an important element in establishing effective communication. Therefore, an Islamic communication strategy that is adaptive to the development of the times, responsive to technological advances, and sensitive to the social character of the millennial generation plays a major role in strengthening Islamic preaching in the modern era.